Global prevalence of Trichinella in pigs: A systematic review and meta‐analysis. Issue 6 (22nd September 2022) - Eslahi, Aida Vafae; KarimiPourSaryazdi, Amir; Olfatifar, Meysam; de Carvalho, Luis Manuel Madeira; Foroutan, Masoud; Karim, Md Robiul; Badri, Milad; Ketzis, Jennifer K.
Abstract: Background: Investigating the global epidemiological patterns of Trichinella in pigs is required for accurate recognition and to establishing proper control programmes and preventive measures, as well as to decrease human exposure. Objectives: To obtain a better understanding of the global prevalence of Trichinella in domestic pigs and factors that might influence the prevalence, a systematic review and meta‐analysis was performed. Methods: The Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines were followed. Multiple databases were used to identify literature published between January 2000 and December 2021, representing studies from 1985 to 2021, on Trichinella prevalence in domestic pigs. Prevalence was calculated on a global and country level, by country Human Development Index (HDI), climate, pig management system, and diagnostic test. Results: The global pooled prevalence based on 60 manuscripts representing 32 countries and 65 pig populations was 2.02% (95% confidence interval [CI]: 0.88–3.62) and the estimated pooled prevalence in different continents ranged from 0.00% to 11.8%. Trichinella was highest in low HDI countries (21.6%; 95% CI: 4.3–47.2), tropical wet climates (20.9%; 95% CI: 10.3–34.1), and non‐intensive pig farming systems (6.1%; 95% CI: 1.0–15.5). Conclusions: While there were regional differences in Trichinella prevalence in domestic pigs, these were likely driven by country HDI and pig farming systems versus climatic factors. Increased biosecurity in outdoor pig production systems, focused meat inspections and promoting awareness could potentially decrease risk of infection. Abstract : Sixty manuscripts representing 32 countries and 65 pig populations qualified for inclusion in this meta‐analysis on Trichinella in domestic pigs. Global pooled prevalence was 2.02% with non‐intensive pig management systems and countries with a lower Human Development Index having higher prevalence.